Comparative study of core materials and multi-degree-of-freedom sandwich piezoelectric energy harvester with inner cantilevered beams - Li, Xiangyang (2021)
Conventional energy harvesters using a single metal substrate can hardly collect sufficient energies from wideband and low frequency vibration sources. A sandwich structure composed of two thin face sheets and a soft-core material can be an alternative substrate to replace a single metal layer to drop the resonant frequency of the harvester accompanied by the increment of the output voltage. The resonant frequency of the sandwich piezoelectric energy harvester (SPEH) can be adjusted more flexibly by selecting the appropriate core material and varying the geometric dimensions of the sandwich substrate. In this paper, a comparative study of different core materials for SPEH is firstly investigated. Prototypes of the SPEHs with different core materials (natural rubber, silicon rubber, polycarbonate plastic) and conventional harvesters with the same geometrical dimension are fabricated and tested. The experiment displays that the plastic sandwich energy harvester is the best of all in terms of voltage output. To extend the application of SPEH to harvester broadband vibration energies, this paper presents a novel multi-degree-of-freedom sandwich energy harvester with inner cantilevered beams to harvester energy from wideband, low frequency and low amplitude vibration sources. The proposed energy harvester comprises of a partitioned main sandwich substrate with a tip mass and two patches of piezoelectric layer bonded on it. Multiple branches with tip masses are extended from the inner substrate. The finite element model of the proposed sandwich harvester is presented to achieve close resonant frequencies in the low frequency range of interest. Then a multi-degree-of-freedom sandwich harvester with inner cantilevered beams is designed, fabricated and tested under. The novel harvester proposed in this paper has high design flexibility to work in various vibration environments.